Valorization of the performance of novel and natural sodium alginate/ pectin/ Portulaca oleracea L. ternary composites in the adsorption of toxic methylene blue dye from the aquatic environment - Sarioz, Neslihan; Isik, Birol; Cakar, Fatih; Cankurtaran, Ozlem (ELSEVIER, 2024)
This research introduces the development of a novel, sustainable, cost-effective, and eco-friendly sodium alginate (SA)-pectin (P) ternary composite, enhanced with Portulaca oleracea L. (PO) additive, which has been thoroughly investigated for its efficacy in removing hazardous methylene blue (MB) dye from wastewater. The selectivity studies using various cationic and anionic dyes were conducted. The composite microbeads that were generated underwent characterization using FTIR-ATR, SEM, XRD, zeta potential, and pHpzcanalysis. Subsequently, the most favorable parameters for adsorption, including initial pH (2-12), contact time (0-180 min), adsorbent dosage (0.01-0.20 g), and temperature (298-318 K), were identified. The effect of monovalent and divalent salt concentrations on adsorption process was evaluated. The adsorption data were utilized in several isotherm (Langmuir, Freundlich, D-R, and Temkin) and kinetic (pseudo-first-order and pseudo-second-order) models. According to the Langmuir isotherm model was calculated the adsorption capacity at 298 K is 709.22 mg/g for SA/ P/PO30 composite microbeads. The process of adsorption was seen to conform to a pseudo-second-order kinetic model. The results revealed that the process was both exothermic (Delta Ho = - 10.42 kJ/mol) and spontaneous (Delta Go = - 26.04 kJ/mol at 298 K). Moreover, reusability analyses demonstrated that the composite microbeads that were created may be utilized several times, even after the 5th cycle. The results indicate that the developed composite microbeads have the potential to serve as an effective and inexpensive adsorbent for eliminating cationic contaminants from a wastewater.
Keywords: Adsorption; Portulaca oleracea L.; Sodium alginate; Pectin; Methylene blue; Microbeads; AQUEOUS-SOLUTION; REMOVAL; Biochemistry & Molecular Biology; Chemistry; Polymer Science